Efektifitas Penerapan Hukuman Tutupan Sunyi Bagi Narapidana (International Forum of Researchers and Lecturers, 2024)
Detention Center/Prison is an institution where defendants who are undergoing trial are held and where criminal sentences are carried out for law violators in Indonesia. In the detention center/prison there are of course rules and regulations that apply to inmates. These provisions are contained in Law 32 of 1995 concerning corrections. Placement in solitary confinement is a form of disciplinary punishment for violators. Silence is given to convicts who are proven to have committed light category offenses more than once or have committed offenses at the moderate level. The aim of implementing silent closure is so that violators can reflect well on their mistakes and are expected not to commit further violations in the future. Because after this, if they commit a violation, the consequences will be more severe.